2014
DOI: 10.1002/14651858.cd000227.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and vitamin D analogues for preventing fractures in post-menopausal women and older men

Abstract: Vitamin D and vitamin D analogues for preventing fractures in post-menopausal women and older men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
326
0
16

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(348 citation statements)
references
References 238 publications
6
326
0
16
Order By: Relevance
“…The authors concluded there is high-quality evidence that vitamin D alone is unlikely to be effective in preventing hip fractures or fracture of any type. However, none of the trials included tested vitamin D3 at doses greater than 800 IU/ day and the authors speculate that higher daily doses may be needed to raise serum 25-hydroxyvitamin D (25(OH)D) concentrations sufficiently [1].…”
Section: An Overview Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded there is high-quality evidence that vitamin D alone is unlikely to be effective in preventing hip fractures or fracture of any type. However, none of the trials included tested vitamin D3 at doses greater than 800 IU/ day and the authors speculate that higher daily doses may be needed to raise serum 25-hydroxyvitamin D (25(OH)D) concentrations sufficiently [1].…”
Section: An Overview Of Evidencementioning
confidence: 99%
“…For vitamin D plus calcium, the Cochrane review concluded there is high-quality evidence that this combination reduces hip fractures by 16% as well as the risk of any type of fracture [1]. A recent systematic review indicated that increasing calcium intake has no effect on fracture risk [6].…”
Section: An Overview Of Evidencementioning
confidence: 99%
“…25,27,28 When vitamin D was combined with calcium, the RR reductions were significant for total or nonvertebral fracture [25][26][27][28][29] and hip fractures, 25,28 with two results non-significant for hip fractures. 26,29 Two of the systematic reviews 26,29 found that higher doses of vitamin D (>400 IU or a median dose of 800 IU) resulted in better and statistically significant RR reductions for nonvertebral and hip fractures.…”
Section: Systematic Reviews/meta-analysesmentioning
confidence: 99%
“…Preventative measures such as exercise, education and vitamin D supplements have been shown to have a non- or inconclusive effect in the residential care facility population (Avenell, Mak, & O’Connell, 2014; Bunn et al, 2014; Cameron et al, 2012). Although a review of complex multifactorial intervention programs has shown a reduction of recurrent fallers (Vlaeyen et al, 2015), there are considerable barriers for implementation outside the highly controlled circumstances of a study (Vlaeyen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%